In ovo toxico-pathological effects of medicinal plants used against coccidiosis on chicken embryos development and hatchability - Ferdinand G. Tchodo; Hervé B. Dakpogan; Benjamin Adjei-Mensah; Ombortime N'nanle; Simplice Karou; Wéré Pitala; Kokou Tona; Batomayena Bakoma (Poultry Science)
TOXICO-pathological effects of herbal plants have always been a major concern, but little information is provided on the toxico-pathological effects of medicinal plants used against coccidiosis. This study aimed to assess the histopathological effects of Carica papaya seeds (CPS), Azadirachta indica leaves (AIL), and Sarcocephalus latifolius root (SLR) used as coccidiostat in traditional poultry farms with various doses using the chick embryo model. A total of 420 Sasso breeder eggs at ED4 of incubation were inoculated with the extract of these plants following a 3×4 factorial design with 3 plant extracts (CPS, AIL and SLR) and 4 inoculation doses (0, 25, 50 and 100 mg/kg egg-weight). From ED6 to ED19, the weights of the albumen and embryo were recorded, and the weights of ED19 embryo organs such as liver, heart, kidney, and lungs were measured. Additionally, histopathological lesions were examined. The results indicated that the presence of various phytoconstituents such as alkaloids, phenolics, flavonoids, tannins, saponins, coumarins, steroids, and triterpenes with statistically significant free-radical-scavenging ability differed among the plant extracts (p < 0.0001). Toxico-pathological examination revealed a dose-dependent slight toxicity (p < 0.0001) of the Azadirachta indica leaves extract compared to the other plants. Additionally, the relative organ weight showed kidney hypertrophy (p = 0.001) and liver hypertrophy (p = 0.0001), as well as dilation of hepatic and cardiac vessels. The conclusion drawn was that chicken embryos are more susceptible to in ovo inoculation with Azadirachta indica leaves compared to Carica papaya seeds and Sarcocephalus latifolius root.